Hubungan Kejadian Hipertensi dengan Kualitas Hidup Penduduk Lanjut Usia di Wilayah Kerja Puskesmas Rijali Desa Batu Merah Kota Ambon Maluku - Zawawi, Wa Ode Meyutya; Kusadhiani, Indrawanti; Siahaya, Presli Glovrig (Jurnal Kesehatan Andalas, 2022)
Hypertension is a degenerative disease that is often encountered in older people. Health status, such as hypertension, can interfere with the quality of life of the elderly. Objective: To determined the relationship between the incidence of hypertension and the quality of life of the elderly in the working area of the Puskesmas Rijali, Batu Merah Village, Ambon City, in 2022. Methods: This study was an observational analytic study with a cross-sectional design and used a consecutive sampling technique in sampling. Results: This study showed that from 76 samples, as many as 40 people (52.6%) suffered from hypertension and 36 people (47.4%) did not. Eight people (10.5%) had poor quality of life and 68 people (89.5%) had a good quality of life. The bivariate analysis results using Chi-square showed a p-value = 0.715 (p > 0,05). Conclusion: It can be said that there is no significant relationship between the incidence of hypertension and the quality of life of the elderly. Further research is needed regarding other factors that affect the quality of life of the elderly such as subject characteristics, medication adherence, and other chronic diseases, which according to several studies, have significance in determining the quality of life.Keywords: elderly, Â hypertension, quality of life